2021
DOI: 10.1016/j.ejvs.2021.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Systematic Review and Meta-Analysis of Sex Specific Differences in Adverse Events After Open and Endovascular Intact Abdominal Aortic Aneurysm Repair: Consistently Worse Outcomes for Women

Abstract: This study demonstrates that the risk of worse outcomes in women (vs. men) after elective abdominal aortic aneurysm repair has not ameliorated with time and the risk ratio for mortality is higher for EVAR than open repair. Sex specific differences varied with type of repair, allowing insight into the increased mortality risk differential for EVAR. Better pre-operative optimisation might reduce the higher risk of systemic complications in women. Arterial injury, renal, and other ischaemic complications (limb an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…In addition, according to Figure 6B , while clinically relevant studies continue to progress, they are being refined to focus on the heterogeneity of different populations, such as octogenarians [ 49 ] and women. Among them, women with AAA rupture have a higher risk of death after EVAR or OR [ 50 ]. New research methods like geometric-biomechanical [ 51 ] and computational mathematics models [ 52 ] are also involved, which can be used to predict AAA rupture, including the assessment of elastic and fluid characteristics, and may provide some value for AAA growth and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to Figure 6B , while clinically relevant studies continue to progress, they are being refined to focus on the heterogeneity of different populations, such as octogenarians [ 49 ] and women. Among them, women with AAA rupture have a higher risk of death after EVAR or OR [ 50 ]. New research methods like geometric-biomechanical [ 51 ] and computational mathematics models [ 52 ] are also involved, which can be used to predict AAA rupture, including the assessment of elastic and fluid characteristics, and may provide some value for AAA growth and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…An example here is the recent updating of a 2010 systematic review evaluating the sex specific operative mortality from intact abdominal aortic aneurysm repair, given the advances in both endograft and imaging technology. 6 , 7 To investigate how factors such as age, sex, ethnicity, and frailty influence clinical outcomes using evidence from both RCTs and observational studies, for example, the influence of age, sex, and contralateral occlusion on stroke and death after carotid endarterectomy or carotid stenting. 8 Presentation of sensitivity analyses to compare information obtained from RCTs vs. observational studies may be illuminating.…”
Section: What Is a Systematic Review And When Is It Useful?mentioning
confidence: 99%
“…An example here is the recent updating of a 2010 systematic review evaluating the sex specific operative mortality from intact abdominal aortic aneurysm repair, given the advances in both endograft and imaging technology. 6 , 7 …”
Section: What Is a Systematic Review And When Is It Useful?mentioning
confidence: 99%
“…A recent meta-analysis of 13 observational studies found an increased risk of death after open surgical repair (OSR) of abdominal aortic aneurysm (AAA) in women vs. men (odds ratio [OR] 1.49, 95% confidence interval [CI] 1.37–1.61). 1 Even after multivariable adjustment for risk factors, female sex is associated with higher peri-operative mortality. 2 , 3 , 4 It has been suggested that differences in the recognition of pre-operative risk or complications may account for the increased mortality, yet it is largely unexplained.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 It has been suggested that differences in the recognition of pre-operative risk or complications may account for the increased mortality, yet it is largely unexplained. 1 In a systematic review comparing baseline comorbidity between women and men undergoing elective OSR for AAA, it was found that women were significantly older at the time of surgery and had diabetes and ischaemic heart disease less often. 5 As the prevalence of AAA is much higher in men than women, the current knowledge of risk factors may be primarily applicable to men.…”
Section: Introductionmentioning
confidence: 99%